Antitumour activity of 1,1-bis-(pyrimidine-2,4-diono-1-il)-2-bromo-2-chloroethylenes substituted molecular complexes and bacterial lectin - E. V. Welchinska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
The aim of research. One of the most successful directions of new antitumour preparations finding is the investigation of antimetabolites of pyrimidin’s and purin’s change which forwards as preformed compounds at the link of biosynthetic processes (DNA, RNA, specific proteins) and brakes tumour’s growth. Molecular complexes on the base of 1,1-bis-[pyrimidine-2’,4’-diono-1’-il]-2-bromo-2’-chloroethylenes and bacterial lectin Bacillus polymyxa were produced with the purpose of new potential antitumour preparation’s obtaining. A purpose of the work is explaining of preformed heterocycles as pyrimidines, investigation of its antitumour activity. Molecular complexes of 1,1-bis-[pyrimidine-2’,4’-diono-1’-il]-2-bromo-2’-chloroethylenes and bacterial lectin Bacillus polymyxa were received.